O (ne)odgovornosti intelektualcev - Rizman, Rudi (Javnost (Ljubljana), 2013)
Drawing on the classification of the roles of intellectuals, the author focuses on the issue to whom and for whom intellectuals are investing their voice. The article discusses several critical issues: firstly, the issue of a gap between theoretical knowledge and practical competences, secondly, the concept of public intellectual, thirdly, Chomsky s paradigm of the responsibility of intellectuals, and fourthly, the historical resonance of intellectuals in the neoliberal imagined society. The author opposes the views that the end of history and the end of ideology terminated the salient role of intellectuals and alternatively builds his argument on their manifold and multiple commitments in the spheres of civil society.The neoliberal order invites in this regard a number of challenges and responsibilities: an opportunity to open up new opportunities for the roles of intellectuals in the imposed market-managed and consequentially structurally changed society. Intellectuals at this very historical moment should turn from mere interpreters to legislators, as Zygmunt Bauman expects them to.
Keywords: intelektualci; družbena vloga; odgovornost